PENGARUH PEMBERIAN PbB ASETAT DOSIS TINGGI TERHADAP KETEBALAN MIELIN N. ISCHIADICUSTIKUS PUTIH (RATTUS NORVEGICUS) - Elfiah, Ulfa (Fakultas Kedokteran Universitas Brawijaya, 2007)
Lead is commonly used in batteries, electrical cabel, and pipe manufacture. Despite its usefulness, lead has some sentrimental effects such as intoxication by chronic lead exposure results in peripheral neuropathy. This research was to determine the effect of oral administration of leadacetate to the thickness of mielin n.ischiadicus. The post test only control group design was used assigning.Thirty male rats into five groups of treatment. Aquadest was administered to group I. Lead acetate with doses of rats were sacrificed: 65, 125, 250, and 500 mg/kgbw/day were administered to group II, III, IV, and V. Lead acetate were given daily for 10 weeks and then to make histological preparations from n.ischiadicus using osmic acid as fixative and toloidin blue as staining agents.The results research showed that oraladministration of lead acetate affected the thickness of mielin with higher does resulted in thinner mielin. Keywords:thickness of mielin, lead acetate, oral